2009
DOI: 10.1590/s1982-56762009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação foliar de silício na resistência da soja à ferrugem e na atividade de enzimas de defesa

Abstract: A ferrugem da soja, causada por Phakopsora pachyrhizi, tem sido controlada pela aplicação de fungicidas devido a indisponibilidade de cultivares resistentes. O silício (Si) tem aumentado a resistência de várias espécies de plantas a patógenos. Assim, este trabalho avaliou o efeito da aplicação foliar desse elemento na severidade da ferrugem e na potencialização da atividade de quitinases, β-1,3glucanases, peroxidases, polifenoloxidases, lipoxigenases e fenilalanina amônia-liases. Plantas de soja (cultivar MG/B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
0
11
0
13
Order By: Relevance
“…Rice and cucumber plants supplied with Si and inoculated with Bipolaris oryzae and Podosphaera xantii, respectively, showed an increase in the activities of POX and CHI (Dallagnol et al, 2011;Liang et al 2005). Pereira et al (2009) reported that soybean plants sprayed with ASM showed reduced symptoms of ASR without any contribution of CHI, GLU, POX, PPO, PAL and lypoxygenase. However, in the present study, plants sprayed with ASM showed an increase in PAL activity at 72 and 141 hai and GLU activity at 72 hai.…”
Section: Discussionmentioning
confidence: 97%
“…Rice and cucumber plants supplied with Si and inoculated with Bipolaris oryzae and Podosphaera xantii, respectively, showed an increase in the activities of POX and CHI (Dallagnol et al, 2011;Liang et al 2005). Pereira et al (2009) reported that soybean plants sprayed with ASM showed reduced symptoms of ASR without any contribution of CHI, GLU, POX, PPO, PAL and lypoxygenase. However, in the present study, plants sprayed with ASM showed an increase in PAL activity at 72 and 141 hai and GLU activity at 72 hai.…”
Section: Discussionmentioning
confidence: 97%
“…The fine powder was homogenized in an ice bath in 15 mL 0.1 M sodium borate buffer (pH 8.8) containing PVPP (1%, w/v). The PAL activity was determined as described by Pereira et al (2009). Four separate extractions were performed for each treatment for assay of the activities of the three enzymes.…”
Section: Silício E Manganês Na Atividade De Enzimas Envolvidas Na Resmentioning
confidence: 99%
“…Four separate extractions were performed for each treatment for assay of the activities of the three enzymes. The protein contents of the extracts were measured according to Pereira et al (2009). A 2 × 3 × 2 factorial experiment, consisting of two Si rates (referred thereafter as -Si and +Si treatments), three Mn rates, and plants inoculated or non-inoculated with B. oryzae was arranged in a completely randomized design with four replications.…”
Section: Silício E Manganês Na Atividade De Enzimas Envolvidas Na Resmentioning
confidence: 99%
“…Em espécies acumuladoras de silício, tais como o trigo, foi verificada a redução do número de lesões e área abaixo da curva de progresso da doença pelo uso de silicato de cálcio (Xavier Filha et al, 2011). Resultados positivos foram obtidos pela pulverização com silicato de sódio e silicato de potássio no controle da antracnose do feijoeiro (Moraes et al, 2006) e da ferrugem da soja (Pereira et al, 2009), respectivamente.…”
unclassified
“…Exemplos do seu emprego auxiliando no aumento de resistência dos tecidos vêm sendo estudados em vários patossistemas (Alvarez & Datnoff, 2001;Moraes et al, 2006, Pereira et al, 2009). Silicato de sódio, de cálcio e de potássio são alguns dos compostos já empregados no controle de doenças (Moraes et al 2006).…”
unclassified